2022
DOI: 10.1002/met.2103
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of global positioning system radio occultation refractivity for the enhanced prediction of extreme rainfall events in southern India

Abstract: Here, we investigated the impact of assimilating the satellite-based product of Global Positioning System (GPS) radio occultation (RO) refractivity profiles data on the simulation of selected extreme rainfall events in three states of southern India: Tamil Nadu, Telangana, and Kerala. We assimilated the GPS RO data into the weather research and forecasting model using a 3DVar assimilation technique and evaluated the results against unassimilated (control) simulations. Various observations (e.g., rainfall measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In addition, because computing bending angles requires a ray tracing model, assimilating of bending angles is computationally very expensive (Liu & Zou, 2003;Shao & Zou, 2002). Therefore, many studies (Boyaj et al, 2022;Chen et al, 2015Chen et al, , 2020Chen et al, , 2021Cheng et al, 2018;Healy et al, 2005;Miller et al, 2023;Singh et al, 2021;Zhou & Chen, 2014), assimilate refractivity using a less computationally expensive observation operator in regional models. We also assimilated refractivities using the computationally affordable 3D-Var assimilation technique due to our limited computational resources.…”
Section: Simulated Observationsmentioning
confidence: 99%
“…In addition, because computing bending angles requires a ray tracing model, assimilating of bending angles is computationally very expensive (Liu & Zou, 2003;Shao & Zou, 2002). Therefore, many studies (Boyaj et al, 2022;Chen et al, 2015Chen et al, , 2020Chen et al, , 2021Cheng et al, 2018;Healy et al, 2005;Miller et al, 2023;Singh et al, 2021;Zhou & Chen, 2014), assimilate refractivity using a less computationally expensive observation operator in regional models. We also assimilated refractivities using the computationally affordable 3D-Var assimilation technique due to our limited computational resources.…”
Section: Simulated Observationsmentioning
confidence: 99%
“…Chang et al (2022) showed that GPSRO refractivity can provide information about the high-moisture level (3-5 km), producing a better heavy rainfall forecast [15]. Boyaj et al (2022) demonstrated the capability of GPSRO refractivity to enhance water vapor condensation and the top levels of ice, cloud, and rainwater, all of which improve hazardous rainfall predictions [16]. Cheng et al (2018) showed that the assimilation of GPSRO refractivity alone enhances both the 24 h and 48 h regional rainfall forecasts, while the assimilation of GPSRO refractivity and conventional observations enhanced the 48 h forecast of light and heavy rain [17].…”
Section: Introductionmentioning
confidence: 99%